Cyclosporin in the management of polymyositis and dermatomyositis. Issue 11 (November 1991) - Lueck, C J; Trend, P; Swash, M
Abstract : Three patients with polymyositis refractory to conventional steroid and immunosuppressive treatment, but responsive to cyclosporin A, are described. In a fourth patient cyclosporin A was used as a first line drug in combination with steroids in the treatment of life-threatening dermatomyositis. Cyclosporin A in the management of polymyositis/dermatomyositis requires formal assessment of its costs and benefits compared with conventional treatments.